Gender, Institutions, and Change in Bachelet’s Chile
XV, 244 p.
Keywords: Michele Bachelet, Chile's first female president, was elected in 2006 with an explicit gender agenda, promising to appoint new faces (including women) to her government and implement some positive gender change. After a period as the first head of UN Women, she was subsequently reelected for a second term in 2013 with a decisive majority. This volume focuses on Bachelet's efforts in both her first and second administrations to introduce progressive measures in Chile and the constraints that she has faced in a context where both formal and informal political institutions can act as barriers to change. Written by leading experts in the field, the chapters highlight both the successes of Bachelet's governments and also the key battles that Bachelet faced, for example with regard to reproductive rights, electoral reform, and social protection.